2016
DOI: 10.1186/s12865-016-0167-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeated cycles of 5-fluorouracil chemotherapy impaired anti-tumor functions of cytotoxic T cells in a CT26 tumor-bearing mouse model

Abstract: BackgroundRecently, the immunostimulatory roles of chemotherapeutics have been increasingly revealed, although bone marrow suppression is still a common toxicity of chemotherapy. While the numbers and ratios of different immune subpopulations are analyzed after chemotherapy, changes to immune status after each cycle of treatment are less studied and remain unclear.ResultsTo determine the tumor-specific immune status and functions after different cycles of chemotherapy, we treated CT26 tumor-bearing mice with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Previous studies in animal models have demonstrated that colon injury is induced by 5-FU and investigated the pathogenetic mechanisms of this damage. [17][18][19][20][21] Therefore, in the present study, we verified that intestinal injury is induced by 5-FU in mice. First, we found that WTAAE protected against 5-FU-induced colon damage using biochemical parameters and histological assessments.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies in animal models have demonstrated that colon injury is induced by 5-FU and investigated the pathogenetic mechanisms of this damage. [17][18][19][20][21] Therefore, in the present study, we verified that intestinal injury is induced by 5-FU in mice. First, we found that WTAAE protected against 5-FU-induced colon damage using biochemical parameters and histological assessments.…”
Section: Discussionsupporting
confidence: 77%
“…16) However, in the clinic, 50-80% of patients who receive 5-FU report considerable side effects, such as diarrhea symptoms and gastrointestinal discomfort. 17) Intestinal injury is a severe limiting factor in clinical applications of 5-FU. 18) Previous studies in animal models have demonstrated that intestinal injury is induced by 5-FU, and the pathogenetic mechanisms of the drug has been investigated in experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…5-FU, an effective and clinical commonly used chemotherapeutic agent, can significantly inhibit the proliferation of tumors, at the cost of reducing the body mass, inducing liver injury, and suppressing the immunological function [ 8 ]. Previous studies have demonstrated liver injury induced by 5-FU in animal models, and most recently, pathogenetic mechanisms of liver injury induced by 5-FU has been investigated in experimental models [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…5-Fluorouracil, a pyrimidine analogue that interferes with thymidylate synthesis, is a basic chemotherapeutic agent for the treatment of colorectal cancer [ 5 , 6 ], however, the development of drug-resistant phenotypes and systemic toxicity, especially liver injury, have become severe limiting factors in 5-FU therapy [ 7 , 8 , 9 ], and thereby 5-FU alone is of limited benefits in enhancing the survival of patients with advanced colorectal cancer. Emerging evidence indicates that 5-FU-induced liver injury is associated with multiple mechanisms, including 5-FU-induced inflammation, oxidative stress, and hepatocyte apoptosis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin inhibits the progression of cancer by inducing DNA damage, whereas the antitumor drug 5‐fluorouracil has toxic effects on cancer cells . Owing to low therapeutic effectiveness, largely attributed to negative side effects of these chemicals, many natural products found in plants have been explored for anticancer therapy …”
Section: Discussionmentioning
confidence: 99%